Platelets activation is associated with elevated plasma mitochondrial DNA during cardiopulmonary bypass. Issue 1 (December 2016) - Qin, Chaoyi; Gu, Jun; Hu, Jia; Qian, Hong; Fei, Xu; Li, Yajiao; Liu, Ruiqi; Meng, Wei
Abstract Background Mitochondrial DNA (mtDNA) was reported as a pro-inflammatory agent. In our previous study, elevation of plasma mtDNA was revealed after cardiac surgery with cardiopulmonary bypass (CPB). Platelets were activated during the cardiac surgery and recent study revealed its ability to release mtDNA. Our present study postulated that the elevated plasma mtDNA comes from activated platelets, which plays a critical role in post-CPB inflammatory responses. Methods Sixty-eight patients who underwent coronary artery bypass graft (CABG) with CPB were enrolled in our study. Blood samples were collected before induction of anaesthesia (T1), at the end of CPB (T2), 12 h post-CPB (T3), 24 h post-CPB (T4), 48 h post-CPB (T5) and 72 h post-CPB (T6). Blood samples were analyzed for the routine blood test and prepared for plasma isolation. MtDNA concentration was measured by rt-PCR, and TNF-α and IL-6 were examined by specific ELISA kits. Subgroup study was analyzed by activation levels of platelet. Basic information, mtDNA level, TNF-α level and IL-6 level were all carefully studied in each quartile. Results Activation level of platelets increased and peaked at T2, which decreased gradually from T3 to T6 (P  < 0.05). MtDNA increased after CPB, peaked at T3, and then backed from T4 to T6 (P  < 0.05). Bivariate correlation between peak activation level of platelets and peak plasma mtDNA level showed a positive correlation between these two parameters (r  = 0.683, P  < 0.0001). Both TNF-α and IL-6 showed similar patterns as mtDNA, with an increase from T1 to T3 and a decrease from T4 to T6 (P  < 0.05). Subgroup analysis further demonstrated that patients with higher activation levels of PLT had higher plasma mtDNA levels and inflammatory level (P  < 0.05). Conclusions Our study revealed the dynamic changes of activation level of platelets and identified the interesting association between platelets activation and plasma mtDNA, suggesting a novel potential mechanism of activated platelets-induced post-CPB inflammatory responses.